Management of Halaqah Tahfidz al-Qur'an in Darut Taqwa Ponorogo Islamic Boarding School - Mustaqim, Moh. Rijal; Maghfiroh, Maghfiroh; Nurhaedha, Hanifah (Universitas Muhammadiyah Magelang, 2020)
The selection of halaqah as the Al-Qur'an's learning system at Darut Taqwa Islamic Boarding School Ponorogo must be able to be an effective, efficient, and productive for learning. Moreover, this research is to strive for good governance. Based on this reason, the research study will focus on the management of halaqah and its thinking towards learning the hafiz of the Qur'an which will encourage qualitative renewal with case study strategies. Furthermore, the findings of the study show that; 1) Halaqah planning is arranged based on planning objectives, materials, strategies, students, and teachers. 2) Organizing halaqah is determined by taking the program, grouping students, and distributing teachers. 3) The implementation of halaqah is carried out with learning, motivation, and supervision by the Qur'an Division. 4) Evaluation is carried out periodically, semesterly, and annually. Meanwhile, the halaqah management is great for students, teachers, and institutions.